Faces of Tradition in Chinese Performing Arts - Gibbs, Levi, 1980- (Book collections on Project MUSE., 2020)
"Faces of Tradition in Chinese Performing Arts examines the key role of the individual in the development of traditional Chinese performing arts such as music and dance. These artists and their artistic works-the "faces of tradition"-come to represent and reconfigure broader fields of cultural production in China today. The contributors to this volume explore the ways in which performances and recordings, including singing competitions, textual anthologies, ethnographic videos, and CD albums, serve as discursive spaces where individuals engage with and redefine larger traditions and themselves. By focusing on the performance, scholarship, collection, and teaching of instrumental music, folksong, and classical dance from a variety of disciplines-these case studies highlight the importance of the individual in determining how traditions have been and are represented, maintained, and cultivated"--